Inclined colloidal drops: Evaporation kinetics and pattern formation - Parsa, Maryam; Askounis, Alexandros (Frontiers in Mechanical Engineering, 2023)
The drying of solute-laden drops is ubiquitous in everyday life, from paints and printers to the raindrops drying on our windows. Nonetheless, scientific interest has primarily focused on understanding the evaporation kinetics on flat surface, with the key parameter of substrate inclination only recently started being addressed. This work focuses on the influence of moderate substrate inclinations at 20o and 40o on the evaporation kinetics and associated deposit patterns of colloidal drops. Inclination altered the shape of the drops which formed a lower contact angle at the upper side of the drop (rear edge) and larger contact angle at the lower side (front edge). As evaporation rate is a function of contact angle, which in turn is a function of inclination, the evaporation lifetime was extended by 43 and 61% for 20o and 40o, respectively, compared to a flat drop. A theoretical approximation of the evaporative flux across the liquid-vapour interface of the drops showed the contribution of each edge to the evaporation kinetics. These differences in the evaporative fluxes altered the internal flows within the drop and in turn the coffee-ring formation mechanism. The particle deposit shape at the two edges for each drop was visualised which combined with the theoretical arguments allowed the proposition of the particle deposition mechanism in inclined drops: inclination added a gravitationally-driven velocity flow component within the drops, which is perpendicular and hence negligible in flat drops. This additional flow hindered or enhanced the number of particles arriving at the rear and front edges of the inclined drops, respectively, and hence influenced the dimensions of the coffee-ring patterns. Eventually, the particle deposits grew sufficiently tall to effectively stagnate the outward flow which resulted in enhanced particle accumulation at the interior of the drops as inclination increased.